Optimization for the extraction of polysaccharides from Huidouba and their in vitro α-glucosidase inhibition mechanism. (October 2022) - Wen, Yuxin; Zhou, Xin; Huo, Da; Chen, Juncheng; Weng, Longmei; Li, Bing; Wu, Zhiqiang; Zhang, Xia; Li, Lin
Abstract : Huidouba is a kind of fungus plant that grows by spiders parasitizing tea trees at an altitude of 1500 m above Mount Emei. The bioactive polysaccharides extracted from Huidouba have been traditionally used in the treatment of diabetes in China. In this study, the optimal hot-water extraction condition of crude Huidouba polysaccharides was obtained using Box–Behnken design: the temperature of 93.7 °C, the time of 3.57 h, the liquid-to-solid ratio of 28.47 mL/g, and the yield was 0.46%. Three purified Huidouba polysaccharides (HDBPs, including HDBP-d, HDBP-1, and HDBP-2) were separated through deproteinization, ultrafiltration, and column chromatography. Then the inhibition mechanism and kinetics of HDBPs against α-glucosidase were investigated. The inhibitory activity of HDBPs on α-glucosidase was positively correlated with their concentration, and their mechanism of quenching fluorescence was ascertained to be the static type induced by the formation of HDBPs-α-glucosidase complex. HDBP-d and HDBP-2 inhibited the activity of α-glucosidase in a reversible competitive-type manner while HDBP-1 was a noncompetitive-type inhibitor. The inhibitory activities of HDBPs on α-glucosidase correlated inversely with temperature in most cases, and showed weaker inhibitory activity at extreme acidic or alkaline conditions. These findings highlight the efficacy, kinetics and mechanism of HDBPs inhibiting α-glucosidase in vitro . The study provided a replaceable approach for chemical inhibitors of α-glucosidase with natural fungus plant extracts, and suggested the theoretical basis that the plant-derived polysaccharides with glucosidase inhibition effects were applied in medicines. Highlights: The optimum hot-water extraction conditions of the CHDBP were obtained. α-Glucosidase activity was inhibited due to the formation of HDBPs-enzyme complex. HDBP-d and HDBP-2 were reversible and competitive inhibitors of α-glucosidase. HDBP-1 was a reversible and non-competitive inhibitor of α-glucosidase. HDBPs showed weaker inhibition activity during extreme TEMP and pH conditions.